ANALISIS IMPLEMENTASI STANDAR PELAYANAN KEFARMASIAN KLINIK DI UPT. PUSKESMAS PAGAR JATI KECAMATAN LUBUK PAKAM - Tarigan, Koko Prananda; Herlina, Herlina; Gurusinga, Rahmad (NHM PRESS, 2023)
Pharmacy practice is carried out based on pharmaceutical service standards in pharmacies, which are set as a reference for the implementation of pharmaceutical services in pharmacies. The purpose of this study was to identify the implementation of clinical pharmacy service standards at UPT. Pagar Jati Health Center, Lubuk Pakam District. This research uses a qualitative research type with a case study approach using interview techniques or in-depth interviews and observation with direct observation using a quality assurance checklist. This research seeks to provide an overview of the management of clinical pharmacy services at UPT. Jati Fence Health Center. The location in this study was the Pagar Jati Health Center, Lubuk Pakam District, Deli Serdang Regency and the time of the research started from the preliminary survey to the research which was carried out from November 2022-April 2023. In this study the researchers used 4 informants, namely the Head of the Puskesmas, the person in charge of pharmacy, Pharmacy staff and puskesmas staff at Pagar Jati Health Center, Lubuk Pakam District, Deli Serdang Regency. In this study, observations were made by observing and observing directly. Analysis in this study used fishbone diagrams or fishbone diagrams. The assessment of the application of pharmaceutical service standards in the aspect of drug administration at the Pagar Jati Health Center, Lubuk Pakam District has gone well, in the aspect of monitoring and evaluation of drugs at the Pagar Jati Health Center, Lubuk Pakam sub-district, it is carried out properly and carried out regularly, monitoring and evaluation of drugs is carried out to ensure certainty the quality and quality of the drugs available, in the aspects of reviewing and submitting prescriptions that have been carried out and carried out well, in the aspects of drug information services have been carried out by the pharmacy team at the puskesmas, but in general the execution of this drug information is still limited to the subject matter of information only medicine, in terms of counseling and visiting aspects technically it has not run optimally, but in carrying out additional activities the puskesmas carries out a home visit service program to community homes, the schedule of these activities is arranged in such a way that it does not interfere with the service schedule in the building at the puskesmas.